Who are we missing? Self-selection bias in nonsuicidal self-injury research. - Robinson K; Dayer KF; Mirichlis S; Hasking PA; Wilson MS (John Wiley and Sons, Inc., 2023)
BACKGROUND: Despite the threat of self-selection bias to the generalizability of research findings, remarkably little is known about who chooses to take part in non-suicidal self-injury (NSSI) research specifically. We aimed to establish the extent of willingness to take part in NSSI research within a commonly sampled population before assessing whether individual differences in demographic characteristics, NSSI lived experience, and participation experiences were associated with willingness to take part in future NSSI research. METHODS: New Zealand university students (n = 3098) completed self-report measures of their NSSI, psychological distress, emotional dysregulation, experience of their participation in the current study, and willingness to participate in future NSSI research. RESULTS: Most participants (78.2%) indicated that they were willing to take part in future NSSI research. Men, older participants, people with NSSI lived experience, and those with more frequent past-year NSSI were more likely to be willing to take part in future NSSI research. Participants who reported a more positive subjective experience of the current study also indicated greater willingness. CONCLUSIONS: Findings demonstrate systematic differences in who is willing to take part in NSSI research. Future research should implement methodological and statistical approaches to mitigate the impact of self-selection bias on NSSI research.
Keywords: Research participation; study recruitment; volunteer bias